Tunable hybrid perovskites with a narrow bandgap and multistage phase transition properties: 2, 2-difluoroethylamine·antimony hexabromide. Issue 21 (17th May 2022) - Song, Ning; Chen, Shaopeng; Fan, Xiaowei; Tan, Yuhui; Tang, Yunzhi; Wang, Lijuan; Liao, Juan; Sun, Zhen
Abstract : An organic–inorganic hybrid perovskite compound, [C6 H18 F6 N3 SbBr6 ] (1 ), with an excellent triple reversible phase transition, dielectric switching properties, and a narrow bandgap of 2.90 eV was synthesized. Abstract : Zero-dimensional perovskites have received extensive attention in recent years due to their unique structural properties, including large exciton binding energies, strong quantum confinement effects, and good stability. Target products were precisely constructed from existing organic–inorganic hybrid perovskite material phase-transition systems via exploiting the ideas of molecular design, modification, and assembly. Herein we report an organic–inorganic hybrid perovskite compound, [C6 H18 F6 N3 SbBr6 ] (1 ), with excellent reversible phase transition and dielectric switching properties. The symmetry of the structure was reduced upon introducing fluorine atoms to the ethylamine moiety. The results showed that compound 1 had a narrow bandgap of 2.90 eV and three distinct dielectric anomalies at ∼175.9, 205.9, and 257.5 K. UV-vis absorption spectra and density-functional theory (DFT) calculations confirmed this bandgap. It was revealed that the octahedral framework of inorganic [SbBr6 ] 3− was the main contributor to this bandgap. This work highlights that the substitution of hydrogen atoms by halogens has important effects on the structural phase transition mechanism and physical properties of the synthesized product, therefore, it provides an effective strategy for the synthesis of novel organic–inorganic hybrid perovskite phase-transition materials.